Students Learning Experience on Technological Based during Learning from Home to Respond Pandemic at Universitas Islam Syekh-Yusuf Tangerang - Andri Kurniawan; Hery Nuraini; Lastry Forsia; Aniek Widiarti; Marrieta Moddies Swara (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This article aimed to analyze the student learning experiences during the pandemic at Universitas Islam Syekh-Yusuf Tangerang. The researchers used a qualitative method. The collecting data used interviews and observation. Interview conducted on several lecturers and academics to get data analysis. Then examined the results of the interviews to get the essence and data findings that could answer the problems of this study and hypotheses. Based on data analysis the researchers concluded that the digital or technology-based learning experience during the remote learning period in response to the pandemic has indicated that learning was exciting because either lecturers and students have established very synergistic collaborations to produce learning quality that was as expected. Therefore, the results of this study could be a meaningful input for future studies. Keywords: Student Learning Experience, Technology Based Learning, Learning From Home